MENINGKATKAN KREATIVIRAS PESERTA DIDIK DALAM MELUKIS MELALUI TEKNIK FINGER PAINTING PADA PELAJARAN SENI RUPA DI SD - Sani Hayati (STKIP Subang, 2023)
This study aims to determine the increase in painting creativity using the Finger Painting Technique for class 3 SD EL-Fitra Antapani Bandung. This research is quantitative with a Quasi Experiment Design research design. This study used two class samples, namely, the Experimental Class and the Control Class with a total of 30 students. The research instrument was in the form of practice questions, then the results of the practice questions were assessed according to creativity indicators and filled in with teacher observation sheets, observation sheets with finger painting techniques. posttest 80.93. Meanwhile, to see the difference in increasing creativity using the Gain Test between the experimental class and the control class, a significant value (2-tailed) was obtained, namely 0.004 <0.05, so H0 was rejected, namely creativity in the experimental class was better than that in the control class. The results of the analysis of data obtained from various tests can be seen that the significance value is more than 0.05 and the significance value of the Difference Test is less than 0.05. The results showed that there was an increase in students' creativity in doing painting with the Finger Pai nting technique in arts and culture subjects in grade 3 and there was a difference in the increase in creativity that occurred between the experimental class and the conventional class. Keywords: Elementary Education, Said Art Education in Elementary School, Finger Pinting